Direct effects of airborne PM2.5 exposure on macrophage polarizations - Zhao, Qingjie; Chen, Hui; Yang, Tao; Rui, Wei; Liu, Fang; Zhang, Fang; Zhao, Yong; Ding, Wenjun (Biochimica et biophysica acta, 2016)
Exposure of atmospheric particulate matter with an aerodynamic diameter less than 2.5μm (PM2.5) is epidemiologically associated with illnesses. Potential effects of air pollutants on innate immunity have raised concerns. As the first defense line, macrophages are able to induce inflammatory response. However, whether PM2.5 exposure affects macrophage polarizations remains unclear. We used freshly isolated macrophages as a model system to demonstrate effects of PM2.5 on macrophage polarizations. The expressions of cytokines and key molecular markers were detected by real-time PCR, and flow cytometry. The specific inhibitors and gene deletion technologies were used to address the molecular mechanisms. PM2.5 increased the expression of pro-inflammatory cytokines granulocyte-macrophage colony-stimulating factor (GM-CSF), interleukin-6 (IL-6), interleukin-1β (IL-1β), tumor necrosis factor alpha (TNFα). PM2.5 also enhanced the lipopolysaccharide (LPS)-induced M1 polarization even though there was no evidence in the change of cell viability. However, PM2.5 significantly decreased the number of mitochondria in a dose dependent manner. Pre-treatment with NAC, a scavenger of reactive oxygen species (ROS), prevented the increase of ROS and rescued the PM2.5-impacted M1 but not M2 response. However, mTOR deletion partially rescued the effects of PM2.5 to reduce M2 polarization. PM2.5 exposure significantly enhanced inflammatory M1 polarization through ROS pathway, whereas PM2.5 exposure inhibited anti-inflammatory M2 polarization through mTOR-dependent pathway. The present studies suggested that short-term exposure of PM2.5 acts on the balance of inflammatory M1 and anti-inflammatory M2 macrophage polarizations, which may be involved in air pollution-induced immune disorders and diseases. This article is part of a Special Issue entitled Air Pollution, edited by Wenjun Ding, Andrew J. Ghio and Weidong Wu. [Display omitted] •Short-term exposure of PM2.5 directly affected macrophage polarization.•PM2.5 treatment increased M1 polarization by ROS pathway.•PM2.5 exposure inhibited M2 polarization partially by mTOR-dependent pathway.